KOREAN REALIA IN INDIRECT TRANSLATION (ON THE NOVEL “THE VEGETARIAN” BY HAN KANG) - Yulia A. Kovalchuk (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
The article presents the results of comparative analysis of the translation of Korean cultural realia of the Man Booker International Prize winning novel “The Vegetarian” by Han Kang in Ukrainian version (2017, transl. A. Asman) and English mediating text (2016, transl. D. Smith). The research proves that the indirect translation of the culture-bound Korean novel from English into Ukrainian leads to inadequacy of translation, distortions of meaning, deterioration of the cultural identity and specificity of the source text. The mistakes of the mediating text are replicated in the target text, as well as new errors and misinterpretations appear, arising from the fact that the Ukrainian translator lacks cultural competence and seeks to domesticate for the target recipient the mediating text, already adapted and transformed. The Ukrainian version of the novel frequently distorts the image of Korean society, violating the norms of Korean etiquette, providing wrong understandings of Korean hierarchical connections and Confucian moral standards. The translation is overloaded with excessively disgusting details depicting the Korean way of life as exotic and “uncivilized”. The artistic ideas of the writer are misrepresented in the Ukrainian translation emphasizing on the differences between Western and Eastern cultures and the issue of the suppression of women in male-chauvinistic conservative society. The misinterpretations impede the readers from focusing on the psychological and philosophical levels of the novel, like the universal problems of solitude, estrangement, social duties and individual freedom. The indirect translation of “The Vegetarian”, performed by a person with insufficient knowledge about Korea, provides the Ukrainian readers with incomprehensible realia without commentaries, unreasonable cultural adaptation, incorrect description of the appearance and motivation of the main characters. The translator was not able to convey the symbolical meaning of many culinary terms and the idea of collective eating as a crucial social phenomenon in Korea. The Ukrainian colloquialisms and slang integrated into the Korean novel make the expressions unnatural and inappropriate to the context. Considering that the source text of the novel “The Vegetarian” is very rich in culinary terms, other cultural words and contexts, and that the general Ukrainian public in not informed about Korean traditions, the book needs a competent translator able to provide comments and perform adequate pragmatic and cultural interpretation.